Kegelschnitte — eine Neubesinnung (mathematica didactica, 2005)
Conic sections do not play any major role in mathematics education today. They should, however as Schupp has pointed out in his “Kegelschnitte”, be revisited in content and applied in line with modern requirements. The following article gives a teaching example and in doing so will demonstrate that conics are very well suited to answer the fundamental didactical question: How do we encourage students to use computers for effective learning?